Aplikasi E-Modul Suhu dan Kalor sebagai Rancangan Bahan Ajar Fisika di SMA - Azmi, Faizatul; Prihandono, Trapsilo; Meilina, Ike Lusi (Universitas Jember, 2024)
Physics learning in SMA Negeri 1 Lumajang often uses textbooks rather than learning modules as learning resources, so it is necessary to develop physics e-modules. This study aims to determine the development design and the validity of physics e-modules of temperature and heat material in senior high school. The research method used is descriptive which describe phenomena or characteristics of the population under the study. The research instrument is a validation questionnaire, interview guidelines, and documentation. The data obtained were the results of validation conducted by 3 expert validators and 2 user validators. The results showed that the average value of the five validators covering four aspect of eligibility namely content, construct, language, the content feasibility aspect gets a score of 83%, the construct feasibility aspect gets a score of 83%, the language feasibility aspect gets a score of 90%, the display feasibility aspect gets a score of 86%. The overall average validation aspects of the five validators get a value of 85,8% with very valid criteria. Based on the research results obtained, it can be concluded that the physics e-module of temperature and heat material gets validity results with very valid criteria and can be tested for development to students at the research school.